A Metabolomic Study of Biomarkers of Habitual Coffee Intake in Four European Countries. Issue 22 (23rd September 2019) - Rothwell, Joseph A.; Keski‐Rahkonen, Pekka; Robinot, Nivonirina; Assi, Nada; Casagrande, Corinne; Jenab, Mazda; Ferrari, Pietro; Boutron‐Ruault, Marie‐Christine; Mahamat‐Saleh, Yahya; Mancini, Francesca Romana; Boeing, Heiner; Katzke, Verena; et al.
Abstract : Scope: The goal of this work is to identify circulating biomarkers of habitual coffee intake using a metabolomic approach, and to investigate their associations with coffee intake in four European countries. Methods and results: Untargeted mass spectrometry‐based metabolic profiling is performed on serum samples from 451 participants of the European Prospective Investigation on Cancer and Nutrition (EPIC) originating from France, Germany, Greece, and Italy. Eleven coffee metabolites are found to be associated with self‐reported habitual coffee intake, including eight more strongly correlated ( r = 0.25–0.51, p  < 10E −07 ). Trigonelline shows the highest correlation, followed by caffeine, two caffeine metabolites (paraxanthine and 5‐Acetylamino‐6‐amino‐3‐methyluracil), quinic acid, and three compounds derived from coffee roasting (cyclo(prolyl‐valyl), cyclo(isoleucyl‐prolyl), cyclo(leucyl‐prolyl), and pyrocatechol sulfate). Differences in the magnitude of correlations are observed between countries, with trigonelline most highly correlated with coffee intake in France and Germany, quinic acid in Greece, and cyclo(isoleucyl‐prolyl) in Italy. Conclusion: Several biomarkers of habitual coffee intake are identified. No unique biomarker is found to be optimal for all tested populations. Instead, optimal biomarkers are shown to depend on the population and on the type of coffee consumed. These biomarkers should help to further explore the role of coffee in disease risk. Abstract : Eleven metabolites measured in serum samples from 451 subjects of the European Prospective Investigation on Cancer and Nutrition (EPIC) study originating from France, Germany, Greece and Italy were found to be associated with coffee intake. They include trigonellline, caffeine and caffeine metabolites, quinic acid, and two diketopiperazines and catechol sulfate derived from coffee roasting. Variations in the magnitude of correlations and of ratios between metabolites indicate differences in the composition of coffee brews consumed by individuals from the four countries.